1999
DOI: 10.1002/jlb.66.3.447
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of monoclonal antibodies EG1 and EG2 with eosinophils and their granule proteins

Abstract: Use of the murine monoclonal antibodies EG1 and EG2 has been based on the assumption that EG2 recognizes activated eosinophils. We examined the reactivity of EG1 and EG2 with eosinophil cationic protein (ECP), eosinophil-derived neurotoxin (EDN), and stimulated and nonstimulated eosinophils from normal donors. By radioimmunoassay, EG1 recognized only ECP, whereas EG2 recognized both ECP and EDN. By Western blot, EG1 reacted with ECP, EG2 reacted with both ECP and EDN, but EG2 could not distinguish between lysa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 28 publications
2
7
0
1
Order By: Relevance
“…All of these changes were confirmed in this study, although markers for eosinophil activation may not be ideal (25). Contrasting these two groups allows for a useful clinical model of increased eosinophilic airway responses and associated airway functional changes.…”
Section: Discussionsupporting
confidence: 57%
“…All of these changes were confirmed in this study, although markers for eosinophil activation may not be ideal (25). Contrasting these two groups allows for a useful clinical model of increased eosinophilic airway responses and associated airway functional changes.…”
Section: Discussionsupporting
confidence: 57%
“…Accordingly, the participation of eosinophils in allergic inflammation is complex, but extracellular tissue deposition of reactive oxygen species and EGPs is their most important local effector function and the result of complete activation with cytolysis 2,4 , 6–8 . It was recently shown that EG2 immunostaining cannot reliably distinguish between activated and resting eosinophils 29,30 . As a consequence, neither the total number nor the number of EG2‐positive eosinophils, but instead the frequency, amount and distribution of extracellular EGP deposition can be considered to be crucial for the evaluation of tissue eosinophilia, at least with respect to activation.…”
Section: Discussionmentioning
confidence: 99%
“…EG2 is a murine monoclonal antibody, and marker of activated eosinophils as it recognizes eosinophil cationic protein [40]. Epidermal staining of HLA-DR was also seen.…”
Section: Clinical Data On Recombinant Ifn-γ (Rifn-γ) Treatment Of Admentioning
confidence: 99%